MATHEMATICAL MODEL OF THE COVID-19 SPREAD WITH TEMPORARY IMMUNITY EFFECTS ON THE VACCINATED AND UNVACCINATED POPULATIONS - MAULIDA HASANAH, SITI
In 2019, there was an outbreak of an infectious disease caused by Severe Acute Respiratory Syndrom Coronavirus 2. The disease causes the so-called COVID-19 disease. This disease is easily contagious and can lead to death, so action is needed to reduce the spread of COVID-19 disease. Self-prevention and vaccines are carried out to give a person immunity. However, vaccines have a duration of immunity. In this Thesis Project, two models have been reconstructed, taking into account the time of vaccine immunity. The model I was formed by dividing the population into vaccinated and unvaccinated people. The model is improved in model II by adding people that lost vaccine immunity. The model analysis on model II found that a short duration of immunity can increase the susceptible population who loses vaccine immunity (Sw). Meanwhile, suppose the rate of disease transmission increases after there is no protection from vaccine immunity. In that case, the number of infected populations will increase with the peak of cases occurring at the end of the year. Therefore, it is necessary to have a booster vaccination policy so that when the booster starts to be implemented, it is seen that the number of infected population and susceptible populations who have lost vaccine immunity is beginning to decrease.